Efisiensi Produktivitas Peralatan Tambang Untuk Mencapai Target Produksi Area (412 Ha) PT. Semen Padang (Persero) Tbk - Hendra Pratama; Murad Murad (Journals Mining Engineering : Bina Tambang, 2019)
Abstract. Production target area (412 ha) which is charged at Limestone Crusher VI of 2,200 tonnes / h while real-time has not been reached, namely 1066.44 tons / hour using a combination of one unit of excavator loading EH 2500-6 to 6 HD conveyance unit 785-7. The research aims to gain the ideal amount of a combination of units excavator loading and transportation to meet the target in the area (412 ha). Type of research is descriptive quantitative empirical approach is through surveys and field observations. Efforts is increase work efficiency by maximizing the available working time in order to maximize productivity. After analyzing the obtained productivity mining equipment increased to 2230.12 tons / hour, then the unit conveyance reduced to 5 units, and the previous match factor MF = 1.44 increase to MF = 0.96 (approaching = 1). Furthermore, the effectiveness rate of 48.47% crusher unit increased to 101.37%.Keywords:  Target Production, Efficiency, Working Time, Productivity, Match Factor